Fugitive Frames: Nomadic semiotics in image analysis - Maria-Carolina Cambre (Aposta)
The history of visual sociology is geographically and temporally dispersed to such a degree that it can be difficult to perceive as a coherent sociological area of study. Add various past cultural and political movements in sociology more broadly, and entire periods of development can be rendered invisible. This article will briefly review some pivotal moments in the Anglo-American record of visual sociology to show how the question of analysis and more specifically image analysis is underdeveloped. By considering the debates in the field, and by looking at the origins and trajectories of possible approaches, we will outline a nomadic semiotic approach using the lens of a specific case study to focus on some essential characteristics and sociological repercussions of the approach in question.